Pengaruh Intellectual Capital dan Corporate Governance terhadap Kinerja Keuangan: Studi Empiris pada Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Aulia Ramadhani; Henri Agustin (Jurnal Eksplorasi Akuntansi, 2021)
The aim of this study was to analyze the influence of intellectual capital, board of commissioners, independent board of commissioner and frequency of commissioners meeting on financial performance. The data used in this study are annual reports In BUMN companies listed on the indonesia stock exchange (idx) in the period 2015-2019. The method of taking data samples using purposive sampling method based on certain criteria. Based on the retrieval method obtained a sample of 21 companies. Hypothesis testing in this study uses multiple linear regression analysis. The results show that frequency of commissioners meeting has no influence on firm value and intellectual capital, board of commissioners and independent board of commissioners have a positive influence on financial performance.